New therapeutic targets for the prevention of infectious acute exacerbations of COPD: role of epithelial adhesion molecules and inflammatory pathways. (25th July 2019) - Atto, Brianna; Eapen, Mathew Suji; Sharma, Pawan; Frey, Urs; Ammit, Alaina J.; Markos, James; Chia, Collin; Larby, Josie; Haug, Greg; Weber, Heinrich C.; Mabeza, George; Tristram, Stephen; et al.
Abstract : Chronic respiratory diseases are among the leading causes of mortality worldwide, with the major contributor, chronic obstructive pulmonary disease (COPD) accounting for approximately 3 million deaths annually. Frequent acute exacerbations (AEs) of COPD (AECOPD) drive clinical and functional decline in COPD and are associated with accelerated loss of lung function, increased mortality, decreased health-related quality of life and significant economic costs. Infections with a small subgroup of pathogens precipitate the majority of AEs and consequently constitute a significant comorbidity in COPD. However, current pharmacological interventions are ineffective in preventing infectious exacerbations and their treatment is compromised by the rapid development of antibiotic resistance. Thus, alternative preventative therapies need to be considered. Pathogen adherence to the pulmonary epithelium through host receptors is the prerequisite step for invasion and subsequent infection of surrounding structures. Thus, disruption of bacterial–host cell interactions with receptor antagonists or modulation of the ensuing inflammatory profile present attractive avenues for therapeutic development. This review explores key mediators of pathogen–host interactions that may offer new therapeutic targets with the potential to prevent viral/bacterial-mediated AECOPD. There are several conceptual and methodological hurdles hampering the development of new therapies that require further research and resolution.